2014
DOI: 10.1016/j.str.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functional Roles of the Accessory I-Domain of Bacteriophage P22 Coat Protein Revealed by NMR Structure and CryoEM Modeling

Abstract: SUMMARY Some capsid proteins built on the ubiquitous HK97-fold have accessory domains that impart specific functions. Bacteriophage P22 coat protein has a unique inserted I-domain. Two prior I-domain models from sub-nanometer cryoEM reconstructions differed substantially. Therefore, the NMR structure of the I-domain was determined, which also was used to improve cryoEM models of coat protein. The I-domain has an anti-parallel 6-stranded β-barrel fold, previously not observed in HK97-fold accessory domains. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
103
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(110 citation statements)
references
References 59 publications
4
103
3
Order By: Relevance
“…During capsid maturation, the D-loops are modeled to pull away from one another, breaking some of these interaction while maintaining interactions just at the D-loop tip (Fig. 1B) (19). In this study, we tested our structural model and showed that residues in the D-loop do play a crucial role in coat protein assembly into procapsids.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…During capsid maturation, the D-loops are modeled to pull away from one another, breaking some of these interaction while maintaining interactions just at the D-loop tip (Fig. 1B) (19). In this study, we tested our structural model and showed that residues in the D-loop do play a crucial role in coat protein assembly into procapsids.…”
mentioning
confidence: 89%
“…P22 coat protein is one of these, as it has a nonconserved accessory domain inserted between the A and P domains (10,17,18). This domain, referred to as the insertion domain (I domain) (19), plays an important role in the folding of coat protein by acting as an intramolecular chaperone (20). The I domain is also involved in determination of capsid size (21) and is hypothesized to stabilize procapsids by forming intersubunit interactions between adjacent capsomers (10,19,20).…”
mentioning
confidence: 99%
See 3 more Smart Citations